Incidence and severity of short‐term incisional complications after intraoperative local infiltration of liposomal bupivacaine in dogs. Issue 4 (16th March 2022) - Power, Ashley M.; McKee, Talon; Jordan, Kara; Bergman, Philip J.; Davis, Kechia M.
Abstract: Objective: To report the incidence of short‐term incisional complications in dogs receiving intraoperative local infiltration of liposomal bupivacaine. Study design: Retrospective study. Animals: Client‐owned dogs ( n  = 218). Methods: Medical records were searched for dogs whose surgical site was infiltrated with liposomal bupivacaine. Records were reviewed for complications within 20 days postoperatively. Cases were categorized by: (1) surgical wound classification (clean, clean‐contaminated, contaminated); (2) labeled versus off‐label use in orthopedic surgery – stifle surgery to address cranial cruciate ligament (CCL) disease versus other orthopedic procedures; and (3) orthopedic versus soft‐tissue surgery. Results: Complications were documented in 43/218 (19.7%) records, including 27/218 (12.4%) complications that resolved spontaneously or with topical treatment. The incidence of short‐term incisional complications did not differ between surgical wound classifications ( P  = 0.55) or between labeled versus off‐label use in orthopedic surgery ( P  = 0.21). Complications seemed more common after soft‐tissue procedures (32/123; 26.0%) than orthopedic procedures (11/95; 11.6%) ( P  < 0.01). Conclusion: Surgical wound classification or type of orthopedic procedure did not seem to influence incisional complications of infiltrated surgical sites. Complications were more common after soft‐tissue procedures than orthopedic procedures. Clinical significance: Infiltration of surgical sites with liposomal bupivacaine seems safe in a broader range of orthopedic procedures than currently labeled. The results also justify further investigation in soft‐tissue surgery.